SASTRA IDEALIS VERSUS INDUSTRI KREATIF: STUDI KASUS FILM NAY SEBAGAI BENTUK FILMISASI NOVEL NAYLA KARYA DJENAR MAESA AYU - Rengganis, Ririe (Jurnal Pena Indonesia, 2017)
Idealism in literary studies often confronted with other interests embedded within the study. In addition to beautiful, literature must have utility for the people who enjoy it in the form of works, among which is a form of (prose) and the film (screenplay and theater). Either in the form of a novel (prose) or in the form of a film, idealism is not to be found entirely because there are some considerations due to the interests attached to them. These considerations include, first, the sensor associated with the norms that exist in people's lives in Indonesia, and secondly, related to the interests of owners of capital to finance the cost of production of the idealistic work to be conveyed to the public audience. Censorship in the film and the work done through the use of language of the author. This is done because the language in the works are an expression of the author as Lacan statement in the theory of subjectivity. In this paper, idealism within Djenar Maesa Ayu (DMA) as the author of the novel Nayla as well as a screenwriter and film director Nay is also expressed through the language of metaphor and metonymy are loaded in order to avoid censorship. The use of metaphor and metonymy that do DMA also consider the norms as reflected in Indonesian society.